Penerapan Good Corporate Governance dalam Pengungkapan Islamic Social Reporting pada Bank Umum Syariah di Indonesia - Pratiwi, Angrum; Darmawati, Darmawati; Amaliyah, Rizky (El-Barka, 2020)
The implementation of Good Corporate Governance (GCG) should be implemented properly, in order to create a healthy banking according to sharia principles. An important part of the governance structure of the Bank is the board of commissioners, directors, and the sharia supervisory board. This study analyzes the effect of GCG disclosure consisting of the board of commissioners, board of directors and sharia supervisory board on Islamic social reporting in Islamic commercial banks in Indonesia. This type of research is associative quantitative. The research sample consisted of seven (7) Islamic commercial banks in Indonesia, with an observation period of 2014-2019. The data source comes from the annual report and GCG report of each Islamic commercial bank. Disclosure of ISR is carried out by means of a dichotomy, namely